TYPE OF FERTILIZATION SYSTEM AS A FACTOR OF CORN YIELD FORMATION ON PODZOLS SOILS - Kolesnyk, Tetiana; Shcherbachuk, Віктор; Kovalchuk, Nataliia (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
Organic fertilization systems of maize on podzol soils formated the high grain yields. The combined using of organic fertilizers with microfertilizers increased the availability of corn origins. The positive influence of organic fertilizer systems on the yield of maize on podzolic soils has been established, is confirmed by the increasing of grain yield to 10,5...13,2 t/ha (+18,4%...+ 48,9% to control (without fertilizers)) and vegetative mass up to 44,1...54,7 t/ha (+11,3%...+38,0% to control). The mineral fertilizer system of maize (N170P70K160) on podzolic soils has ensured the formation of high grain yield at a level of 12.8 t / ha (+ 43.8% for control) and 55.9 t / ha of vegetative mass (+41.2 % to control). The organic fertilizer system with granulated poultry manure (5,9 t/ha) created a tendency of maize yield increasing compared to the mineral system (N170P70K160). Feeding of maize by microfertilizer created the effect of corn yield increasing by 10,3%...15,7% on the variants of organic fertilizer systems based on the cattle manure and fermented compost Biopropherm. Among the four types of comparable organic fertilizers (cattle litter manure, vermicompost, granulated poultry manure Plant Feed, fermented compost Biopropherm), granulated poultry manure Plant Feed (5,9 t / ha) has the highest efficiency of maize yields formation. All organic fertilizer systems were less effective compare to the granulated poultry manure system: vermicompost – by 7.99%, fermented compost Biopropherm – by 13.9%, and cattle litter manure – by 20.5%. In a dry, critical period of maize nutrition, it has been experimentally proved the feasibility of combining organic fertilizer systems with micronutrient fertilization (cattle manure and fermented compost Bioproferm). It increased the grain yield by 10.3% and 15.7% and vegetative mass by 5.2% and 17.0% additionally. Maize feeding with microfertilizers on the background of organic fertilizer systems contributed to an increasing of seedling availability by 13.3% ... 45.5% relative to organic fertilizer systems without microfertilizers.